2014
DOI: 10.1021/ct401035t
|View full text |Cite
|
Sign up to set email alerts
|

Parametrization of an Orbital-Based Linear-Scaling Quantum Force Field for Noncovalent Interactions

Abstract: We parametrize a linear-scaling quantum mechanical force field called mDC for the accurate reproduction of nonbonded interactions. We provide a new benchmark database of accurate ab initio interactions between sulfur-containing molecules. A variety of nonbond databases are used to compare the new mDC method with other semiempirical, molecular mechanical, ab initio, and combined semiempirical quantum mechanical/molecular mechanical methods. It is shown that the molecular mechanical force field significantly and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 110 publications
1
67
0
Order By: Relevance
“…12,23 mDC and X-Pol are conceptually equivalent but differ in their details of how the fragments interact with one another. The X-Pol method interacts the fragments using a traditional QM/MM potential; however, this potential depends upon which fragment is considered to be the QM region.…”
Section: Development Of a Qmff Based On The MDC Methodsmentioning
confidence: 99%
“…12,23 mDC and X-Pol are conceptually equivalent but differ in their details of how the fragments interact with one another. The X-Pol method interacts the fragments using a traditional QM/MM potential; however, this potential depends upon which fragment is considered to be the QM region.…”
Section: Development Of a Qmff Based On The MDC Methodsmentioning
confidence: 99%
“…Consequently, it has been shown that water clusters lose their hydrogen bond angles, instead choosing to adopt TIP3P-like, 133 planar hydrogen bonding motifs. 21,59,61 To correct for this deficiency, the mDC method concocts a new, auxiliary atomic multipole representation of the fragment density that is solely used for the inter-fragment Coulomb interactions.…”
Section: Inter-fragment Coupling Schemesmentioning
confidence: 99%
“…54 This approach has been adopted in the present work. In essence, a second set of atomic charges and higher-order atomic multipoles are chosen to interact with the implicit solvent response, while leaving the DFTB3 solute-solute interactions unchanged from their original form.…”
Section: A Solute Charge Density Interaction Correctionmentioning
confidence: 99%
“…The implicit solvent model response is caused by the electrostatic potential of the solute; therefore, an auxiliary set of atomic multipole moments from the DFTB3 density matrix was constructed using the prescription developed in Ref. 54. The inclusion of these multipole moments leads to the alleviation or complete elimination of these systematic errors, thus informing the decision to abandon parameterization efforts using the conventional DFTB3 monopole approximation.…”
Section: A Vr-scosmo Model Parameterizationmentioning
confidence: 99%